2016
DOI: 10.18632/oncotarget.11652
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor ARF regulates tissue microenvironment and tumor growth through modulation of macrophage polarization

Abstract: Tumor microenvironment has been described to play a key role in tumor growth, progression, and metastasis. Macrophages are a major cellular constituent of the tumor stroma, and particularly tumor associated macrophages (TAMs or M2-like macrophages) exert important immunosuppressive activity and a pro-tumoral role within the tumor microenvironment. Alternative-reading frame (ARF) gene is widely inactivated in human cancer. We have previously demonstrated that ARF deficiency severely impairs inflammatory respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Monocyte-macrophage lineage derives from myeloid precursors in bone marrow and subsequently develop as tissues-specific macrophages in response to local microenvironment signals [ 1 , 2 ]. Macrophages are heterogeneous and pleiotropic cells which can be generally polarized into M1-(classically activated) or M2-(alternatively activated) subtypes, which is a continuum of diverse functional states [ 3 , 4 ]. M1 phenotype could be triggered by lipopolysaccharide (LPS) and/or interferon (IFN)-γ andis believed to exert pro-inflammatory effects on tissue injury [ 5 , 6 ], which have the specific markers such as inducible NO synthesase (iNOS), interleukin(IL)-12 [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Monocyte-macrophage lineage derives from myeloid precursors in bone marrow and subsequently develop as tissues-specific macrophages in response to local microenvironment signals [ 1 , 2 ]. Macrophages are heterogeneous and pleiotropic cells which can be generally polarized into M1-(classically activated) or M2-(alternatively activated) subtypes, which is a continuum of diverse functional states [ 3 , 4 ]. M1 phenotype could be triggered by lipopolysaccharide (LPS) and/or interferon (IFN)-γ andis believed to exert pro-inflammatory effects on tissue injury [ 5 , 6 ], which have the specific markers such as inducible NO synthesase (iNOS), interleukin(IL)-12 [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, ARF was also shown to be transcriptionally induced in response to IFNs and viral stimulation (44,45). The significant p53-independent contribution of ARF to the innate immune response has since been highlighted by several studies (5,6,46,47). Proof of concept for ARF as a sensor and responder to viral stress was provided when García et al (5) demonstrated that ARF protects cells and mice from the infection of IFN-sensitive viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they were polarized to produce the immunosuppressive and proangiogenic cytokines commonly associated with the maintenance of a protumor microenvironment. Arf-null tumors preferably recruited such macrophages to increase angiogenesis and promote their growth (46,47). Importantly, Arf-null mice were remarkably less able to recruit neutrophils and monocytes to the site of drug-induced peritonitis (6).…”
Section: Discussionmentioning
confidence: 99%
“…P16 binds to cyclin-dependent kinases 4 and 6 (CDK4 and CDK6) and inhibits phosphorylation of Rb, which remains associated with the transcription factor, E2F. Alternate reading frame protein (ARF) complexes with mouse double minute 2 homolog 2 (MDM2), an E3 ubiquitin ligase that regulates the stability of p53 and therefore suppressing tumor growth, it is also involved in the immune response, by modulating the tumor environment [46]. Therefore, mutation(s) in alternate reading frame protein dysregulate p53 function and play a role in tumor immune evasion.…”
Section: Molecular Pathwaysmentioning
confidence: 99%